A nanographene disk rotating a single molecule gear on a Cu(111) surface. (1st February 2022) - Lin, H-H; Croy, A; Gutierrez, R; Joachim, C; Cuniberti, G
Abstract: On Cu(111) surface and in interaction with a single hexa-tert-butylphenylbenzene molecule-gear, the rotation of a graphene nanodisk was studied using the large-scale atomic/molecular massively parallel simulator molecular dynamics simulator. To ensure a transmission of rotation to the molecule-gear, the graphene nanodisk is functionalized on its circumference by tert -butylphenyl chemical groups. The rotational motion can be categorized underdriving, driving and overdriving regimes calculating the locking coefficient of this mechanical machinery as a function of external torque applied to the nanodisk. The rotational friction with the surface of both the phononic and electronic contributions is investigated. For small size graphene nanodisks, the phononic friction is the main contribution. Electronic friction dominates for the larger disks putting constrains on the experimental way of achieving the transfer of rotation from a graphene nanodisk to a single molecule-gear.